Impact of Heuristics on Investment Decisions: The Moderating Role of Locus of Control - Dangol, Jeetendra; Manandhar, Rashmita (Journal of Business and Social Sciences Research, 2020)
This paper aims to assess the impact of heuristics on the investment decision by analysing the effect of four heuristic biases, i.e., representativeness, availability, anchoring and adjustment, and overconfidence bias on rationality of Nepalese investor's investment decision-making and also examines the moderating effect of the internal locus of control in between. The study used 391 respondents based on a convenient sampling procedure, and structured questionnaire survey. The study result indicates that there is a significant relationship between irrationality in investment decision-making and all four heuristic biases. In addition, the study also concludes that locus of control has significant moderating effect in the relationship between investment decisions and three heuristic biases, i.e., availability, representative and anchoring bias. However, the study documents no moderation effect in case of relationship with overconfidence bias.